TINJAUAN YURIDIS ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK SEBAGAI DASAR PEMBATALAN KEPUTUSAN TATA USAHA NEGARA DALAM KAITANNYA DENGAN PASAL 53 AYAT (2) UNDANG-UNDANG NOMOR 9 TAHUN 2004 - Laratmase, Kristhiana Anthonia (Mimbar Keadilan, 2016)
Badamai at Banjar Adat community is the implementation of Islamic moral value that have always taught the way of peace or islah in resolving a dispute. Badamai in inheritance disputes prevalent in Banjar society islah way. Similarly in the case of dispute resolution such as divorce marital reconciliation, separate beds (barambangan), including the division of joint property badamai finish (treasure continence) during the marriage in the event of divorce or because of divorce life, this is often done by attempting to reconcile through roles (hakamain). The results of this research are: (1) the division of the community estate in Banjar performed usig an agency called islah, which is essentially the institution determines each part of the theirs and other beneficiaries by consensus. In the role of institutions islah master teacher and close relatives are parents is crucial. Therefore there is the role of master teacher, then the provisions of Islamic aw into their benchmark. But under normal circumstances (no inheritance dispute) the division of inheritance is done varies, at least in two ways, Fara’id-Islah ad second Islah way, and (2) how to completion of the distribution of the estate is done in a family that is by agreement of the heirs based on a custom badamai valid for the Banjar, a wise solution to address the differences in economic conditions heirs. Waris Distribution Agreement in principle heir to the principle of division of real kinship is based on the belief of the scholars of fiqh that matter the beneficiary is an individual right which shall have the right to use or not use its right, or use their rights in a particular way while not harming others in accordance with the standard rules apply in ordinary circumstances.